Are the spatial features of bodily threat limited to the exact location where pain is expected? - Vanden Bulcke, C; Crombez, G; Spence, C; Van Damme, S (Elsevier, 2014)
Previous research has revealed that anticipating pain at a particular location of the body prioritizes somatosensory input presented there. The present study tested whether the spatial features of bodily threat are limited to the exact location of nociception. Participants judged which one of two tactile stimuli, presented to either hand, had been presented first, while occasionally experiencing a painful stimulus. The distance between the pain and tactile locations was manipulated. In Experiment 1, participants expected pain either proximal to one of the tactile stimuli (on the hand; near condition) or more distant on the same body part (arm; far condition). In Experiment 2, the painful stimulus was expected either proximal to one of the tactile stimuli (hand; near) or on a different body-part at the same body side (leg; far). The results revealed that in the near condition of both experiments, participants became aware of tactile stimuli presented to the "threatened" hand more quickly as compared to the "neutral" hand. Of particular interest, the data in the far conditions showed a similar prioritization effect when pain was expected at a different location of the same body part as well as when pain was expected at a different body part at the same body side. In this study, the encoding of spatial features of bodily threat was not limited to the exact location where pain was anticipated but rather generalized to the entire body part and even to different body parts at the same side of the body.